2017
DOI: 10.5847/wjem.j.1920-8642.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of modified Alvarado scoring system and RIPASA scoring system as diagnostic tools of acute appendicitis

Abstract: BACKGROUND: Acute appendicitis is the most common surgical condition presented in emergency departments worldwide. Clinical scoring systems, such as the Alvarado and modified Alvarado scoring systems, were developed with the goal of reducing the negative appendectomy rate to 5%-10%. The Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) scoring system was established in 2008 specifi cally for Asian populations. The aim of this study was to compare the modifi ed Alvarado with the RIPASA scoring system in Ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 12 publications
3
49
2
7
Order By: Relevance
“…9 The infectious etiology, differential diagnosis and management for perforated appendicitis and non-perforated appendicitis are current hot topics. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Since the appendix is connected to cecum which is exposed to the environment outside of human body, appendicitis can be caused by different etiologies. Therefore, appendicitis should not be only one entity, but a group of different entities.…”
Section: Introductionmentioning
confidence: 99%
“…9 The infectious etiology, differential diagnosis and management for perforated appendicitis and non-perforated appendicitis are current hot topics. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Since the appendix is connected to cecum which is exposed to the environment outside of human body, appendicitis can be caused by different etiologies. Therefore, appendicitis should not be only one entity, but a group of different entities.…”
Section: Introductionmentioning
confidence: 99%
“…2 In some cases diagnosis is difficult despite it's a common problem in health sector especially in adult, young and reproductive female because host of another gynecological and genitourinary tract may present with similar symptoms. 3,4 In many previous studies authors concluded that negative appendectomy is a better option than the fear of perforation which is a more serious complication. 5 Diagnostic accuracy may be improved with use of computed tomography and utrasonography but here is another risk of early appendectomy which can be resolved conservatively.…”
Section: Introductionmentioning
confidence: 99%
“…A scoring system developed by Alvarado in 1896, on the basis of eight predictive clinical factors to improve the accuracy of physician's clinical assessments in diagnosing acute appendicitis. [8][9][10][11][12] It was 10-point scoring system includes clinical symptoms, signs and laboratory findings, where Alvarado recommended an operation for all patients with score 7 or more. [9][10][11][12] Later in 1994, the last point of the original score was omitted.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] It was 10-point scoring system includes clinical symptoms, signs and laboratory findings, where Alvarado recommended an operation for all patients with score 7 or more. [9][10][11][12] Later in 1994, the last point of the original score was omitted. 13 Nowadays the Modified Alvarado Score has been widely assessed as to its accuracy in the preoperative diagnosis of acute appendicitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation